Chemotherapy‐induced alopecia management: Clinical experience and practical advice. (2nd February 2017) - Rossi, Alfredo; Fortuna, Maria Caterina; Caro, Gemma; Pranteda, Giulia; Garelli, Valentina; Pompili, Umberto; Carlesimo, Marta
Summary: Background: Chemotherapy‐induced alopecia (CIA) is probably one of the most shocking aspects for oncological patients and underestimated by physicians. Among hair loss risk factors, there are treatment‐related aspects such as drug dose, administration regimen, and exposure to X‐rays, but also patient‐related characteristics. To the best of our knowledge, no guidelines are available about CIA management. Aims and methods: With this study, based on literature background and our clinical experience, we would like to propose a list of actions in order to estimate the risk of hair loss before starting chemotherapy and to manage this condition before, during, and after drug administration and to create a sort of practical guide for dermatologists and oncologists. Results and conclusion: There is an urgent need for prospective studies to clarify the mechanistic basis of alopecia associated with these drugs and consequently to design evidence‐based management strategies.